Improving SMEs Performance Based on Strategy Management - Lucky Hikmat Maulana (Technium Business and Management, 2023)
The existence of Micro, Small, and Medium Enterprises (SMEs) in economic growth, employment, and national income is the main reason for making it a priority for government and community attention. The research is oriented to determine and analyze the improvement in MSME performance through strategic management approaches, government policies, and the involvement of stakeholders. The research used quantitative methods, regression coefficient analysis, correlation, and determination. The research results show that there is government involvement as a regulator in guiding SMEs, through Law No. 20 of 2008 and other regulations. Stakeholder involvement in the form of coaching, training, mentoring, funding, and partnerships plays an important role in improving the performance of SMEs. SMEs feel that there is a revision of regulations regarding SMEs. These regulations are oriented towards supporting MSME activities to create a conducive SME business atmosphere. Efforts to empower MSMEs by stakeholders should be comprehensive, coordinated, and sustainable.